Diseño e Implementación de un Sistema de Monitoreo en Tiempo Real de los Parámetros de Variables Electro Energéticas de los Equipos de Control y Respaldo de Energía Eléctrica del Sistema Integrado de Seguridad ECU 911 Loja. - Cosme Xavier, Gálvez Sánchez (2019)
The purpose of this research project is to develop a real-time monitoring system that allows visualizing the electro-energetic parameters of the internal electrical network of the SIS ECU 911 Loja building. The electrical system of the ECU 911 Loja, is currently integrated with electric power control and backup equipment, which is in charge of the supervision and control of said system. The proposal of this thesis, has to develop a software that allows access to the electro-energetic variables measured by these equipments, through a human-machine interface or HMI, by its acronym in English human machine-interface. This thesis begins with a brief study of the monitoring and control systems used in the industry, better known as SCADA systems, by acquiring the knowledge to design and implement the proposed monitoring system. Then, it proceeds to the collection of information from the work field, as well as the equipment that intervenes in it. Finally, making use of free software tools, which are detailed below, the monitoring system is developed and implemented, which deals with the present project.